(untitled) (Nigerian Journal of Technology, 2025)
Deep beams are favorable in resisting high load creating shear due to their reduced span to depth ratio; nonetheless, they are known to produce diagonal shear brittle failure under service load including its own weight. A lightweight structure is required to reduce the overall load. In this study, seven lightweight deep beams were constructed using expanded polystyrene (EPS) as a partial replacement of coarse aggregate in concrete at 20% and 30%. The density of the EPS beams is 10.5% lower than that of the control beams. To increase shear behavior and comprehend deep beam failure under monotonic loading, 0.4% waste tire steel fiber by volume of concrete was incorporated in the concrete mix. Although the compressive and tensile strengths of control beams were higher than those of the EPS beam, reducing the weight of the beam by 20% EPS with tire fiber can improve both deep beam capacity and ductility. The capacity and ductility were 1% and 57% higher, respectively, than the control beam. Beams with tire fiber were also found to have a rough large crack width due to strain hardening characteristic, which allows them to withstand more load. This phenomenon is critical for structures in service.